Firing tax vs. severance payment: An unequal comparison - Dennis Wesselbaum (Kiel Institute for the World Economy (IfW), 2010)
Empirical evidence indicates that lay-off costs consist of two elements, namely firing costs and severance payments. This paper investigates business cycle and steady state effects of firing costs and severance payments and discusses the differences. We find that severance payments imply a lower volatility of key labor market variables compared with firing costs. Persistently increasing those costs, reduces the welfare in the model economy but increases employment. The reason for the different performance is the impact on the wage and the additional stimulus caused by severance payments. The social planner therefore faces a trade-off in the design of employment protection. Furthermore, the design of lay-off costs also has strong implications for the design of other elements of employment protection.
Keywords: D61; E24; E32; 330; Firing Costs; Severance Payments; Welfare; Kündigung; Kosten; Abfindung; Arbeitnehmerschutz; Wohlfahrtseffekt; Arbeitsmarktflexibilisierung; Theorie